Backwater - Bauer, Joan (Penguin, 2005)
While compiling a genealogy of her family of successful attorneys, 16-year-old history buff Ivy Breedlove treks into the mountain wilderness to interview a reclusive aunt with whom she identifies and who in turn helps her to truly know herself and her family.